Impact of trade facilitation indicators on trade flows in transport corridors of CAREC region and policy implications - Falendra Kumar Sudan; Balwant Singh Mehta (Asian Development Bank Institute (ADBI), 2024)
The development of transport corridors and better trade facilitation enhance cross-border trade flows and stimulate economic integration via stronger regional cooperation. Against this backdrop, this paper intends to analyze the effect of trade facilitation indicators (TFIs) on trade flows in the Central Asia Regional Economic Cooperation (CAREC) transport corridors and offer policy implications for strengthening trade facilitation. Using the Corridor Performance Measurement and Monitoring TFIs database, an augmented gravity model has been estimated to examine the effect of TFIs on bilateral trade flows in the CAREC countries along CAREC transport corridors. The study reveals that the TFIs in CAREC corridors have generated a considerable positive impact on bilateral trade flows of the CAREC economies though fluctuated over time. Trade times and longer time delays can increase trade costs and lower trade. Transaction delays and insufficient information, longer physical inspections, inadequate coordination, and lengthy customs procedures can negatively impact inbound trade flows. Longer customs clearance hampers the quality and prices of agricultural exports. The heterogeneity in the TFIs along CAREC corridors is considerable and likely to have a significant positive impact on bilateral trade flows in the CAREC economies. With stronger TFIs, regional integration and cooperation among CAREC corridor economies along the routes is being bolstered. With better TFIs in CAREC corridor economies, inward trade flows are likely to decline comparatively higher than the surge in outward trade flows. The bilateral trade inflows are likely to boost trade volume and can be used for the development of infrastructure and natural resources. Therefore, there is a need to support the CAREC corridor economies to vigorously contribute to the development of transport corridors and improve the TFIs for robust trade performance. Stronger regional economic cooperation should promote the development of novel technologies, skills, and knowledge in order to improve the TFIs further for better trade performance.
Keywords: F13; F14; M48; P25; R41; 330; trade facilitation indicators; trade flows; transport corridors; CAREC region; policy implications